Transcription factor lineages in plant-pathogenic fungi, connecting diversity with fungal virulence - John, Evan; Singh, Karam; Oliver, Richard; Tan, Kar-Chun (Elsevier, 2022)
Plant-pathogenic fungi span diverse taxonomic lineages. Their host-infection strategies are often specialised and require the coordinated regulation of molecular virulence factors. Transcription factors (TFs) are fundamental regulators of gene expression, yet relatively few virulence-specific regulators are characterised in detail and their evolutionary trajectories are not well understood. Hence, this study compared the full range of TFs across taxonomically-diverse fungal proteomes and classified their lineages through an orthology analysis. The primary aims were to characterise differences in the range and profile of TF lineages broadly linked to plant-host association or pathogenic lifestyles, and to better characterise the evolutionary origin and trajectory of experimentally-validated virulence regulators. We observed significantly fewer TFs among obligate, host-associated pathogens, largely attributed to contractions in several Zn2Cys6 TF-orthogroup lineages. We also present novel insight into the key virulence-regulating TFs Ste12, Pf2 and EBR1, providing evidence for their ancestral origins, expansion and/or loss. Ultimately, the analysis presented here provides both primary evidence for TF evolution in fungal phytopathogenicity, as well as a practical phylogenetic resource to guide further detailed investigation on the regulation of virulence within key pathogen lineages.